Wideband variable-gain amplifiers based on a pseudo-current-steering gain-tuning technique - Kong, Lingshan (2020)
This paper reports two variable-gain amplifiers (VGAs) featuring a new pseudo-current-steering gain-tuning technique. In the first VGA (VGA-I), a single-voltage-controlled dual-branch current mirror is exploited as a standalone gain control block. In the second VGA (VGA-II), two NMOS transistors, which are biased by a tunable voltage, are integrated into a conventional common-source amplifier to steer away partial of the total current. Fabricated in 40-nm CMOS technology, the VGA-I (VGA-II) occupies a tiny area of 0.03 mm 2 (0.024 mm 2 ) and consumes 22 mW (20 mW). Measured over a gain range of > 64 dB, the -3-dB bandwidth of the VGA-I (VGA-II) is 9 GHz (6.6 GHz). For the time-domain tests, VGA-I (VGA-II) exhibits a jitter of 40 ps (30 ps), under a 2 7 -1 PRBS input at 12 Gb/s. Their power efficiencies (1.83 and 1.67 pJ/bit) compare favorably with state-of-the-art wideband VGAs.